SIMULATION MODELING OF WORK STABILITY OF STATE-PRIVATE PARTNERSHIP IN CONSTRUCTION - Natalya V. Gorodnova (Advanced Engineering Research)
Urgency of the problem on the theory development of the organization and control of the state-private partnerships in the investment and building sphere is shown. The simulation modeling of the sustainable development and efficient management of the state-private partnerships is run.